Cloning and characterization of EgGDSL, a gene associated with oil content in oil palm - Zhang, Yingjun (2018)
Oil palm (Elaeis guineensis, Jacq.) is a key tropical oil crop, which provides over one third of the global vegetable oil production, but few genes related to oil yield have been characterized. In this study, a GDSL esterase/lipase gene, which was significantly associated with oil content, was isolated from oil palm and designated as EgGDSL. Its functional characterization was carried out through ectopic expression in Arabidopsis ecotype Col-0. It was shown that expression of EgGDSL in Arabidopsis led to the increased total fatty acid content by 9.5% compared with the wild type. Further analysis of the fatty acid composition revealed that stearic acid (18:0) increased in the seeds of the transgenic lines, but the levels of linoleic acid (18:2) plus 11-eicosenoic acid drastically declined. Quantitative real-time PCR (qPCR) revealed that in oil palm, EgGDSL was highly expressed in mesocarp followed by leaf, and the expression level was very low in the root. The expression level of EgGDSL gene began to increase at two months after flowering (MAF) and reached its peak by four MAF, then declined rapidly, and reached its lowest level during the mature period (6 MAF). The EgGDSL gene was more highly expressed in oil palm trees with high oil content than that with low oil content, demonstrating that the transcription level of EgGDSL correlated with the amount of oil accumulation. The gene may be valuable for engineering fatty acid metabolism in crop improvement programmes and for marker-assisted breeding.